Odpowiedzi

2009-12-04T21:42:54+01:00
2009-12-04T21:49:07+01:00
Odpowiedź "b"
Sprawdzenie :

Dla punktu A
f(x)= 0,5(-2) + 5
f(x)= -1 + 5
f(x)= 4

Dla punktu B
f(x)= 0,5(2) + 5
f(x)= 1 + 5
f(x)= 6
2009-12-04T21:51:56+01:00
A)f(x)=x + 6

A=(-2,4)
f(-2)= -2+6
f(-2)=4

B=(2,6)
f(2)= 2+6
f(2)=8

b)f(x)=0,5x + 5
A=(-2,4)
f(-2)= 0,5×(-2)+5
f(-2)= -1+5
f(-2)= 4

B=(2,6)
f(2)= 0,5×2+5
f(2)= 1+5
f(2)=6

c)f(x)=2x + 2
A=(-2,4)
f(-2)= 2×(-2)+2
f(-2)= -4+2
f(-2)= -2

B=(2,6)
f(2)= 2×2+2
f(2)= 4+2
f(2)= 6

Poprawną odpowiedzią jest odpowiedź b).